2019
DOI: 10.1002/bdd.2210
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profile analyses for inhaled drugs in humans using the lung delivery and disposition model

Abstract: The kinetic clarification of lung disposition for inhaled drugs in humans via pharmacokinetic (PK) modeling aids in their development and regulation for systemic and local delivery, but remains challenging due to its multiplex nature. This study exercised our lung delivery and disposition kinetic model to derive the kinetic descriptors for the lung disposition of four drugs [calcitonin, tobramycin, ciprofloxacin and fluticasone propionate (FP)] inhaled via different inhalers from the published PK profile data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has to be noted that, even when selecting the right model for a drug with non-absorptive loss, the parameter estimation process resulted in unidentifiable parameters. Sakagami et al suggested that this instability can be circumvented by fixing the lung dose [ 31 ]. However, this requires detailed information about the lung dose, which is subject to great variability, both between subjects and between occasions [ 9 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that, even when selecting the right model for a drug with non-absorptive loss, the parameter estimation process resulted in unidentifiable parameters. Sakagami et al suggested that this instability can be circumvented by fixing the lung dose [ 31 ]. However, this requires detailed information about the lung dose, which is subject to great variability, both between subjects and between occasions [ 9 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous modeling approaches either reduced the given complexity or lack adequate model evaluation. For example, the mucociliary clearance was described as a first-order process [15,16]. Other published population PK models did not differentiate between undissolved and dissolved drug and consider pulmonary drug absorption as a "one-way process", i.e.…”
Section: Introductionmentioning
confidence: 99%